KAJIAN POTENSIAL OSMOTIK DAN DURASI OSMOCONDITIONING TERHADAP DAYA HANTAR LISTRIK DAN KANDUNGAN KIMIA BENIH KACANG MERAH YANG TELAH MENGALAMI DETERIORASI - Yosefina Lewar; Yohanes Dimu Heo; Senny J. Bunga (Partner, 2016)
Using quality seeds could increase crop production, including kidney bean, "Inerie", cultivar. The qualified seeds providing enough food supply in the endosperm as a primary energy for a normal and strong germination (viability) and seedling growth (vigor). Seeds from harvested yield are stored for the next planting season. During storage the quality of the seeds will be deprived physically, physiologically and chemically, impact on the production. One way to overcome the drawbacks of the deteriorated seeds is by osmoconditioning using Polyethylene Glycol solution. Osmoconditioning strongly influenced by the osmotic potential and duration of osmoconditioning. The results showed that: 1) Osmoconditioning using PEG-6000 during invigoration affect the electrical conductivity and the chemical content of seeds, which has been deteriorating during 1 year storage; and 2) There is an interaction between osmotic potency and duration of osmoconditioning using PEG-6000 in relation to the electrical conductivity and chemical composition on the seed during 1 year storage. -1.0 MPa with 1 hour osmoconditioning gave the best effect on the electrical conductivity, the levels of free fatty acids and P-total of the â€œInerieâ€ seeds.Keywords: Kidney bean, osmotic potency, duration of osmoconditioning, deterioration, Polyethylene Glycol.